Simultaneous Determination of Residues of New Quinone Outside Inhibitor Fungicides Mandestrobin and Metyltetraprole in Fruits and Vegetables by QuEChERS Coupled with Ultra-high Performance Liquid Chromatography-Tandem Mass Spectrometry - ZHOU Wenjing, WANG Luyan, ZHOU Changyu, FANG Nan, ZHANG Changpeng, JIANG Jinhua (Shipin Kexue, 2025)
A method for the detection of the residues of two new quinone outside inhibitor (QoI) fungicides, mandestrobin and metyltetraprole, in six common types of fruits and vegetables (celery, cucumber, corn, grape, strawberry and peach) was developed by quick, easy, cheap, effective, rugged and safe (QuEChERS) combined with ultra-high performance liquid chromatography-tandem mass spectrometry. Samples were extracted with acetonitrile and further purified with a mixture of 25 mg of N-propylethylenediamine, 2.5 mg of polycarbonate and 150 mg of anhydrous magnesium sulfate. The chromatographic separation was accomplished on a Waters Acquity UPLC® BEH C18 column (2.1 mm × 100 mm, 1.7 μm) using a mobile phase consisting of 0.1% formic acid and acetonitrile. The results showed that the calibration curves of mandestrobin and metyltetraprole exhibited a good linear relationship in the concentration range of 0.005–0.5 mg/L, with correlation coefficients ranging from 0.995 2 to 0.999 9, and the limit of quantification (LOQ) was 0.01 mg/kg for both analytes. At three spiked levels of 0.01, 0.1 and 0.5 mg/kg, the average spiked recovery rates of mandestrobin and metyltetraprole ranged from 84.0% to 107.0% and 84.0% to 104.0%, respectively, with relative standard deviations (RSDs) ranging from 3.7% to 18.3% and 3.9% to 14.7%, respectively. This method is rapid, accurate, sensitive, and suitable for simultaneous quantification of mandestrobin and metyltetraprole residues in fruits and vegetables, providing technical support for the detection and risk assessment of the novel QoI fungicides mandestrobin and metyltetraprole in agricultural products.